Consumer Satisfaction towards Online Shopping: A Study of Purchasing Alternatives in Beni Bazaar, Western Hill Nepal - Ghimire, Bhola Nath (Myagdi Guru, 2024)
Understanding the factors that influence consumer satisfaction is crucial for online shopping businesses aiming to enhance their competitive edge. This study identifies seven different factors that affect consumer satisfaction in online shopping settings. Prior research regarding consumer satisfaction in online shopping has been done mainly in urban settings and developed countries. This study aims to fill this gap by exploring the factors of consumer satisfaction in online shopping/purchasing an iternatine in the local context of Beni Bazaar. For collecting the primary data, the structured questionnaire was distributed to people from a diverse sample of online shoppers through convenience sampling. The study is based on sixty-two respondents from this area. Descriptive research design was used as the research method for quantitative analysis and positivism was used as the research paradigm. Statistical methods like Kaiser-Meyer-Olkin (KMO), factor extraction, Mean, SD and Variance were used to make analysis and draw conclusions. The results show that all seven factors are positively related among which trustworthiness and pricing were the most significant factors of consumers’ satisfaction. The findings of this study can be beneficial to researchers, businesspeople, and local government for policy-making as well as academic purposes.